2011
DOI: 10.1097/aln.0b013e31820efafd
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Blockade of Sevoflurane Postconditioning Is Not Restored by Insulin in the Rat Heart

Abstract: The effective reduction in infarct size and apoptosis in the nondiabetic rat heart by postC was completely abrogated in diabetic rats. This inhibition is not relieved by insulin-induced normoglycemia. The PI3K pathway and mitochondrial adenosine triphosphate-dependent potassium channel activation are involved in the mechanism of postC. In diabetic rats, STAT3 activation was strongly reduced, as was postC cardioprotection, suggesting that the inability of insulin to restore postC may be attributed to diabetes-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 44 publications
(46 reference statements)
3
46
0
Order By: Relevance
“…However, in most cases, the cardioprotective effects of anaesthetics including isoflurane have been shown to be diminished or even abolished in hearts from individuals with diabetes [2,6]. Hyperglycaemia-induced oxidative and nitrosative stress, increased quantities of circulating inflammatory cytokines and dysfunction of mitochondrial K ATP channels are all plausible factors to explain the susceptibility of diabetic hearts to IRI [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in most cases, the cardioprotective effects of anaesthetics including isoflurane have been shown to be diminished or even abolished in hearts from individuals with diabetes [2,6]. Hyperglycaemia-induced oxidative and nitrosative stress, increased quantities of circulating inflammatory cytokines and dysfunction of mitochondrial K ATP channels are all plausible factors to explain the susceptibility of diabetic hearts to IRI [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Reperfusion restores coronary flow, phenomenon is termed 'isoflurane postconditioning' (IsoPostC) [3]. However, the cardioprotective effects of volatile anaesthetic postconditioning are attenuated or abolished in rabbits [4] and mice [5] with hyperglycaemia or in individuals with diabetes [6], and the mechanism is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Blood glucose levels were controlled between 3.9 and 5.8 mmol/L with the following regimen: 3 U/d of intermediate-acting insulin was administered 48 h before cardiac ischemia, and 2U of short-acting insulin was administered 1 h before the experiment (Drenger et al, 2011). The Krebs-Henseleit solution was supplemented with the HIF-1α-specific inhibitor 2-methoxyestradiol 15 min prior to reperfusion (Si et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…However, the protective effects of SPC are lost under diabetic conditions (Drenger et al, 2011; Tai et al, 2012), and the mechanisms are poorly understood. It has been reported that under diabetic conditions, the hypoxia-inducible factor-1alpha (HIF-1α) signaling pathway is damaged (Heather and Clarke, 2011; Xiao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The restoration of cardioprotection from ischaemic postconditioning with return to normoglycaemia, through transplantation of islet cells, has been identified in a type 1 diabetic mouse model study [116]. In a separate rat study, however, insulin pretreatment had very different findings, with no restoration of cardioprotective effects from ischaemic postconditioning [139]. …”
Section: Difficulties In Clinical Translation Of Ischaemic Conditionimentioning
confidence: 99%